2019
DOI: 10.1002/dc.24347
|View full text |Cite
|
Sign up to set email alerts
|

Risk of malignancy in “atypia of undetermined significance” category of salivary gland fine‐needle aspiration: A bi‐institutional experience

Abstract: BackgroundMany prior institutional and multi‐institutional studies have applied the Milan System for Reporting Salivary Gland Cytopathology (MSRSGC) retrospectively to their specimens to determine the risk of malignancy (ROM) of each category. Most of these studies focused on general assessment of the system and risk classification. However, there seems to be less focus on the category of atypia of undetermined significance (AUS) that could be attributed to the low number of cases that could fit into this cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…Similar to previous reports, nearly one‐half of the AUS samples in the current study were lymphocyte‐rich aspirates, with the majority of cases representing non‐Hodgkin lymphoma 9,13‐15 . The most common reason to classify an aspirate containing lymphocytes as AUS was a lack of a monomorphic population as well as the presence of only rare atypical lymphocytes, which should be interpreted with caution because reactive lymphoid tissue and chronic sialadenitis can demonstrate similar cytomorphologic features.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar to previous reports, nearly one‐half of the AUS samples in the current study were lymphocyte‐rich aspirates, with the majority of cases representing non‐Hodgkin lymphoma 9,13‐15 . The most common reason to classify an aspirate containing lymphocytes as AUS was a lack of a monomorphic population as well as the presence of only rare atypical lymphocytes, which should be interpreted with caution because reactive lymphoid tissue and chronic sialadenitis can demonstrate similar cytomorphologic features.…”
Section: Discussionsupporting
confidence: 85%
“…This is not surprising because the ROM for the AUS category was not a well‐defined entity by the time the MSRSGC was published because there was a lack of literature regarding salivary gland aspirates classified as AUS. Since then, more studies have shown that the ROM for AUS was higher and ranged from 34% to 44% 9‐12 …”
Section: Discussionmentioning
confidence: 99%
“…In recent research, Alruwaii et al [30] observed prominent lymphocytic components in 50% of cases in the AUS category and reported that most of them were lymphoma, reactive lymphoid tissue, or sialadenitis. In the present study, 5 lymphocytic lesions were observed in AUS (5/31, 16.1%): 2 cases of low-grade lymphoma, 2 lymphocytic sialadenitis, and 1 follicular hyperplasia (Table 5).…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Results of several studies that analysed distribution of cases and estimated ROM in each MSRSGC category show that FNA cytology is an effective diagnostic procedure and confirmed the validity and diagnostic utility of MSRSGC, further revealing that ROMs of each category were broadly in line with those suggested in MSRSGC. In some of these studies, higher ROM for AUS category than in MSRSGC was observed, which probably resulted from the lower number or heterogeneity of AUS patients in these studies …”
Section: Diagnostic Accuracy Of Cytopathology For Salivary Gland Lesimentioning
confidence: 92%